PAW29 Multiple sclerosis in Ireland: regional variation in prevalence and vitamin D status. Issue 11 (22nd October 2010) - Lonergan, R; Jordan, S; Hagan, R; Kinsella, K; Fitzpatrick, P; Duggan, M; Murray, B; McKenna, M; Hutchinson, M; Tubridy, N; Brady, J; Dunne, C
Abstract : Introduction: Reports suggest increasing multiple sclerosis (MS) prevalence, which distinctively rises with latitude. Genetic factors contribute but vitamin D deficiency is a possible co-factor. Hypotheses: In Ireland, vitamin D is lower in MS patients than in controls. Greater prevalence at higher latitudes corresponds to lower vitamin D levels. Prevalence is greater than in 2001. Patients and Methods: Patients and controls in Donegal, Wexford and South Dublin attended research clinics from November 2007 to March 2008. Blood samples were taken for vitamin D and PTH measurement, and DNA extraction. Results: Prevalence significantly increased in Donegal (northwest) (290.3/100 000) compared with 2001 (184.6/100 000, p<0.001). Prevalence is significantly higher in Donegal than in Wexford (southeast) (144.8/100 000, p<0.0001) and South Dublin (127.8/100 000, p<0.0001). Overall, mean vitamin D levels were low and did not differ significantly between patients (38.57 nmol/l) and controls (36.41 nmol/l; winter normal >50 nmol/l). However, more patients had vitamin D levels <25 nmol/l, p 0.004. Levels were significantly higher in South Dublin (area with lowest MS prevalence) (mean 50.74 nmol/l, p<0.0001). HLA DRB1*15 occurred most frequently in Donegal. Conclusion: Vitamin D insufficiency is common in Ireland. Latitudinal variation in MS probably relates more to genetic factors than to vitamin D levels alone, but risk may be modified by vitamin D in genetically susceptible individuals.